Booster vaccination against the SARS-CoV-2: mechanisms and efficiency - S. A. Berns; A. V. Veremeyev; A. A. Savicheva; A. Yu. Gorshkov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2023)
Coronavirus disease 2019 (COVID-19) pandemic was not only a serious challenge for the healthcare system around the world, but also an incentive for intensive research and development for the introduction of innovative technologies and drugs, in particular vaccines against the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2). The first vaccination campaigns provided significant protection against severe disease course and hospitalization. However, new SARS-COV-2 variants require further comprehensive research and the introduction of booster vaccination. Booster vaccination is the most important tool for immunostimulation and increase of protection duration against the severe disease course. The study of booster vaccines, including BioNTech/Pfizer, Moderna, Oxford AstraZeneca, Sputnik V, Sinopharm и Covaxin vaccines, sheds light on their unique action mechanisms and contribution to long-term immunity. The analysis of clinical data demonstrates their effectiveness and safety. The review summarizes modern knowledge about booster vaccinations against the COVID-19 with focus on action mechanisms and efficiency. In addition, the immune system function in response to COVID-19 is considered, while the role of memory cells, antibody and cellular immunity reactions are emphasized.